2013
DOI: 10.1136/amiajnl-2011-000796
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation of a biomedical informatics course for medical students: challenges of a large-scale blended-learning program

Abstract: Biomedical informatics (BMI) competencies are recognized as core requirements for the healthcare professional, but the amount of BMI educational interventions in the curricula of medical schools is limited. UNAM Faculty of Medicine in Mexico is a large public medical school, with more than 7000 undergraduate students. The undergraduate program recently underwent a major curricular revision, which includes BMI education. Two one-semester BMI courses (BMI-1 and BMI-2) were designed, with a blended-learning educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 18 publications
0
35
0
8
Order By: Relevance
“…Students described both F2F and TEL activities positively but highlighted that F2F and TEL activities should be complementary, rather than TEL used simply to replace F2F sessions. Getting the right "blend" of F2F and TEL activities is integral to the success of a BL course (43). Other research also found that F2F activities followed by TEL activities leads to students engaging with the content more than students access to only TEL activities (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students described both F2F and TEL activities positively but highlighted that F2F and TEL activities should be complementary, rather than TEL used simply to replace F2F sessions. Getting the right "blend" of F2F and TEL activities is integral to the success of a BL course (43). Other research also found that F2F activities followed by TEL activities leads to students engaging with the content more than students access to only TEL activities (44).…”
Section: Discussionmentioning
confidence: 99%
“…Positive interactions with lecturers can improve student learning (51,52) as one-on-one direction can assist individual students learning needs, such as help in prioritising and clarifying course content. Students also value being part of a learning community, as F2F sessions in BL courses can foster a community spirit that encourages students to learn through supported interaction with teachers and their peers (43). Virtual learning environments design can maximise student-teacher interaction through discussion boards and email.…”
Section: Discussionmentioning
confidence: 99%
“…15 La Facultad de Medicina de la Universidad Nacional Autónoma de México (UNAM) es una escuela pública, fundada hace más de cuatro siglos, con más de 7,000 estudiantes de pregrado y, fuente principal mexicana de profesionales y académicos. Al realizar una revisión curricular se consideró necesario un cambio, por lo que resulto el Plan de Estudios 2010, llevado a cabo desde el año académico 2010-2011, 26 el cual está organizado por asignaturas con un enfoque por competencias. 27 El Aprendizaje Autorregulado y permanente, es una de ellas pero hasta el momento no se cuenta con un instrumento que permita evaluarla y en consecuencia se carece de información sobre las habilidades de autorregulación de los estudiantes.…”
Section: Introductionunclassified
“…One of the benefits of using computers is that expert intervention systems like CDSS are able to integrate elements (Praveen et al, 2014). CDSS decisions are part of a set of options available to professionals and are based on actual human knowledge established by previously defined rules (Sánchez-Mendiola et al, 2013), which is possible because these expert systems focus on a delimited area of knowledge.…”
mentioning
confidence: 99%